Geomorphological evolution in transitional environments on the eastern coast of Brazil - Moreira, Vinícius Borges [UNESP]; Lämmle, Luca; Torres, Bruno Araújo; Donadio, Carlo; Perez Filho, Archimedes (Wiley, 2024)
The morphology of the coastal landscape in transitional environments results from the gradual and complex dynamics of natural processes at different scalarity, capable of elaborating and remodeling the relief. Their arrangements and interactions are reflected in the configuration and evolution of the landscape and waterscape governed by allogenic factors (climate, tectonics and, more recently, anthropogenic) generating autogenic responses in environmental systems. In this sense, several studies have demonstrated the importance of sea level oscillations, sedimentary balance and river-coastline displacements associated with climate fluctuations during the Quaternary. However, there is still a relative lack of recent research that focuses on the last glacial maximum (LGM) and the Holocene for the eastern Brazilian coast. In this way, the intense morphodynamics between estuarine and deltaic systems could become interpretative keys in the general understanding of these environments worldwide because they are located in a particular context within the connectivity of these geomorphological systems. To investigate these processes between the Jequitinhonha, Pardo and Una Rivers, detailed mapping and geomorphic topographic profiles were carried out using pre-selected digital elevation models, and fieldworks were carried out on land and water to validate the mappings and to collect samples. Then, they were subjected to geochronological analysis using Optically Stimulated Luminescence and grain size distribution to recognize the depositional age and characterize the surficial cover. It was possible to identify five depositional landscape units: fluvial terraces, fluvial-marine terraces and three staggered levels of marine terraces. Based on these results, a paleogeographic reconstruction of the evolutionary phases of this eastern sector of Brazil's coast was carried out, chronologically covering the Pleistocene/Holocene transition up to the present. The aim is to understand littoral dynamics as a response to both fluvial adjustments and oscillations of the regional relative sea level.
Keywords: coastal geomorphology; landscape evolution; OSL Dating; Quaternary deposits; transitional environments